2021
DOI: 10.1186/s12967-021-02922-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mediators of lymphangiogenesis in inflammatory bowel disease

Abstract: Background Recent studies reporting the intricate crosstalk between cellular and molecular mediators and the lymphatic endothelium in the development of inflammatory bowel diseases (IBD) suggest altered inflammatory cell drainage and lymphatic vasculature, implicating the lymphatic system as a player in the occurrence, development, and recurrence of intestinal diseases. This article aims to review recent data on the modulatory functions of cellular and molecular components of the IBD microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 139 publications
(164 reference statements)
0
11
0
Order By: Relevance
“…However, it is questionable whether H89 has an anti-inflammatory function (prevention of chemically induced carcinogenesis) or a proinflammatory function (by inducing IFN-γ). In our case, H89 induced IFN-γ (a proinflammatory cytokine essentially secreted by TLs and NK cells) which can induce an antitumor effect, unlike proinflammatory cytokines released by, e.g., neutrophils or monocytes, involved in inflammatory bowel disease (IBD) (for review: 40 ). Our results also revealed that the involvement of an adaptive response of the antitumor effect of H89 may be related to its ability to reduce the expression of PD-L1 and CD80 on cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…However, it is questionable whether H89 has an anti-inflammatory function (prevention of chemically induced carcinogenesis) or a proinflammatory function (by inducing IFN-γ). In our case, H89 induced IFN-γ (a proinflammatory cytokine essentially secreted by TLs and NK cells) which can induce an antitumor effect, unlike proinflammatory cytokines released by, e.g., neutrophils or monocytes, involved in inflammatory bowel disease (IBD) (for review: 40 ). Our results also revealed that the involvement of an adaptive response of the antitumor effect of H89 may be related to its ability to reduce the expression of PD-L1 and CD80 on cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…The conclusion that IMCs can promote lymphangiogenesis have wider implications than in just regeneration. Lymphangiogenesis has been shown to be involved the development of breast cancer, colon cancer metastasis, and inflammatory bowel disease (Nandi et al, 2017; Ocansey et al, 2021; Tacconi et al, 2015). Thus, given their role in promoting LEC activation and sprouting by producing PGE2, it may be worth investigating the role of IMCs in these other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic vessels contribute to human diseases such as cardiovascular disease (28), renal fibrosis (29), interstitial lung disease (30), cancer metastasis (31) and inflammatory bowel disease (32). The features of chronic inflammation include lymphangiogenesis and blood vessel remodeling (33).…”
Section: Discussionmentioning
confidence: 99%